Road traffic noise, noise sensitivity, noise annoyance, psychological and physical health and mortality - Stansfeld, S; Clark, C; Smuk, M; Gallacher, J; Babsich, W (BioMed Central, 2021)
Background Both physical and psychological health outcomes have been associated with exposure to environmental noise. Noise sensitivity could have the same moderating effect on physical and psychological health outcomes related to environmental noise exposure as on annoyance but this has been little tested.